Order fulfillment in high variety production environments - MacCarthy, Bart L.; Brabazon, P.G.
Providing high levels of product variety and product customization is challenging for many companies. This paper presents a new classification of production and order fulfillment approaches available to manufacturing companies that offer high variety and/or product customization. Six categories of approaches are identified and described. An important emerging approach - open pipeline planning – is highlighted for high variety manufacturing environments. It allows a customer order to be fulfilled from anywhere in the system, enabling greater responsiveness in Build-to-Forecast systems. The links between the open pipeline approach, decoupling concepts and postponement strategies are discussed and the relevance of the approach to the volume automotive sector is highlighted. Results from a simulation study are presented illustrating the potential benefits when products can be reconfigured in an open pipeline system. The application of open pipeline concepts to different manufacturing domains is discussed and the operating characteristics of most relevance are highlighted. In addition to the automotive, sectors such as machinery and instrumentation, computer servers, telecommunications and electronic equipment may benefit from an open pipeline planning approach. When properly designed these systems can significantly enhance order fulfillment performance.